URGENSI PEMBATASAN MASA JABATAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAN DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA - Ferdy Putra Ernawan; Ahmad Sholikhin Ruslie (Gapenas Publisher, 2023)
This study aims to provide a limitation on the need for rules that limit the periodization of the term of office of DPR and DPD members. In many cases, people who have been in power for a long time abuse their power. Type of Research This type of research is normative legal research or library research, namely research conducted using literature, either in the form of books, scientific journals, mass media and the internet as well as other references. There is a legal issue, so there needs to be a rule limiting the periodization of the term of office for members of the DPR and DPD. In many cases, people who have been in power for a long time abuse their power. Whoever holds power and no matter how well it is executed, has the seeds of potential power or ability as Lord Acton's classic saying about power tends to corrupt, but absolute power corrupts absolutely meaning,“power tends to corrupt, and absolute power must corrupt absolutely”. undeniable. Government administrators place themselves above the people and regard themselves as the source of all prevailing order. Revisions to the terms of office for the DPR and DPD need to be realized immediately, bearing in mind the urgency in terms of legal justice, the poor dimension of democracy, and leadership regeneration. In order to fulfill the need to realize an electoral system based on a democratic constitution